Маркетинг в управлінні підприємствами машинобудування - Нехай, Вікторія Василівна; Волкова, С. О.; Nekhai, Viktoriia; Volkova, Sofia (Запоріжжя : ТДАТУ, 2023)
UA: Стаття торкається питань впровадження та організації маркетингу підприємствами машинобудування. Метою статті є узагальнення наукових доробок та досвіду впровадження та організації маркетингу на машинобудівних підприємствах для розв’язання пріоритетних завдань удосконалення управління підприємствами та розвитку економіки України. Набуло подальшого розвитку обгрунтування доцільності використання інноваційного підходу до розв'язання проблем запровадження маркетингу. EN: The article deals with the implementation and organization of marketing by machine-building enterprises. The purpose of the article is to generalize scientific developments and experience in the implementation and organization of marketing at machine-building enterprises to solve an important scientific problem - the development of theoretical and methodological principles and methodological tools for improving economic activity. As a result of the conducted empirical research and logical generalization, patterns and principles of marketing activity were revealed, and new scientific knowledge regarding the marketing paradigm was formed. It has been proven that domestic science has formed a conceptual vision of a fundamentally new course of modernization transformations in Ukraine and specific mechanisms for their implementation. The imperfection of management technologies is indicated, which negatively affects the development of domestic machine-building enterprises; The concept of marketing was improved, which was embodied in the justification of the feasibility of using such forms of marketing as indirect (through cooperation with traders) and direct (organization of departments, departments, bureaus) with the aim of establishing the marketing of a machine-building enterprise, which should become, at the same time, both practical and scientific complex activity to solve economic problems. As a result of the conducted empirical research and logical generalization, regularities and principles of marketing activities at enterprises for the production of industrial goods were revealed, and new scientific knowledge regarding the marketing paradigm was formed. It is promising to further research individual aspects of the introduction of marketing at enterprises of various branches of the economy of our country, to study the experience of solving this problem at domestic and foreign enterprises in order to develop the newest forms of introducing the marketing concept into the activities of modern enterprises.
Marketing in the management of engineering enterprises
Keywords: конкурентоспроможність; маркетинг; машинобудування; ринкові відносини; трейдер; управління; competitiveness; marketing; market relations; mechanical engineering; management; trader